REPRESENTATIONS OF MEGACITY AND SOCIAL-PSYCHOLOGICAL SATIETY OF YOUNG CITY DWELLERS WITH LIVING CONDITIONS - Drobysheva , T.V.; Larionov , I.V. (Modern Psychology, 2021)
The article deals with the problem of the relationship between social and psychological satiety and social ideas about the metropolis. The contradictory perception of young people living conditions in a metropolis is explained by the fact that the core and periphery of social representation include judgments of different modality. A connection was found between elements of the periphery of representation and indicators of socio-psychological satiety. It is shown that the satiety of young people with living conditions in the city is associated with their perception of the problematic aspects of life in the metropolis. The choice of strategies for coping with the state of satiety is determined by the respondents' experience of a range of negative emotions and feelings.
Keywords: social-psychological satiety; social perceptions; social psychology of the city